2000
DOI: 10.1007/s004499900106
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Zn(II) by Thiobacillus ferrooxidans

Abstract: There have been a number of studies considering the possibility of removing and recovering heavy metals from diluted solutions. These are due, principally, because of the commercial value of some metals as well as in the environmental impact caused by them. The traditional methods for removing have several disadvantages when metals are present in concentrations lower than 100 mg/l. Biosorption, which uses biological materials as adsorbents, has been considered as an alternative method. In this work, variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Although q m and b are affected by a number of factors, the pH of the adsorption system is likely to exert the greatest in¯uence and hence Table 2 also lists the pH values under which the q m and b values were measured, permitting a meaningful comparison of the relative effectiveness of different adsorbents. Note that the trend of the pH effect on zinc adsorption reported in studies using algal and bacterial biosorbents 13,16 is in agreement with that observed in the present study. It appears that the extent of zinc adsorption increased with increasing pH regardless of the adsorbent used.…”
Section: Adsorption Equilibriumsupporting
confidence: 94%
“…Although q m and b are affected by a number of factors, the pH of the adsorption system is likely to exert the greatest in¯uence and hence Table 2 also lists the pH values under which the q m and b values were measured, permitting a meaningful comparison of the relative effectiveness of different adsorbents. Note that the trend of the pH effect on zinc adsorption reported in studies using algal and bacterial biosorbents 13,16 is in agreement with that observed in the present study. It appears that the extent of zinc adsorption increased with increasing pH regardless of the adsorbent used.…”
Section: Adsorption Equilibriumsupporting
confidence: 94%
“…The maximum sorption capacity of the monolayer increased with increasing temperature (20- 24 , and Chen et al 35 and Nasernejad et al 36 , using Y. lipolytica ISF7, Saccharomyces cerevisiae, brown alge Padina australis, bacteria Pseudomonas putida, and carrot residues as biosorbents, respectively. A much lower maximum sorption capacity was observed by Sari et al 20 and Celaya et al 37 who used Cladonia furcata and Thiobacillus ferrooxidans; the corresponding values were 7.9 mg/g (nickel) and 9.7 mg/g (zinc). On the other hand, a higher biosorption of Ni(II) was observed by Shinde et al 3 and Suazo-Madrid et al 31 , at 48.3 and 112.9 mg/g, respectively, using Y. lipolytica and Rhodotorula glutinis as biosorbents.…”
Section: Biosorption Isotherm Modelsmentioning
confidence: 76%
“…Therefore, much attention has been paid to the removal of metal ions by microorganisms owing to its potential applications in environmental protection and recovery of toxic or strategic heavy metals (Tsezos, 1985;Fourest and Roux, 1992;Chang and Hong, 1994;Puranik and Paknikar, 1999;Celaya et al, 2000;Liu et al, 2002). Microbiologists have discovered several bacterial species with applications in mining and recovery of radioactive waste, known as bioleaching and bioremediation, respectively (Lovley, 2003;Liu et al, 2004).…”
Section: Role Of Chemolithotrophic Bacteria In Biomachiningmentioning
confidence: 99%